Differential growth of Leptosphaeria maculans in the stem of susceptible and partially resistant oilseed rape (Brassica napus L.) genotypes. Issue 4 (4th July 2022) - Levrel, Anne; Lemoine, Jocelyne; Ermel, Magali; Abu-Ahmad, Youssef; Gravot, Antoine; Delourme, Regine
Abstract: Quantitative resistance (QR) to Leptosphaeria maculans in Brassica napus has proven to be very useful for breeding resistant varieties with increased potential for durability. To date, however, QR has been assessed primarily in the field after a long plant developmental cycle and its expression is influenced by environmental conditions. An evaluation method in controlled conditions would offer the possibility to evaluate the level of QR in a shorter time and to study the kinetics of fungal growth in the stem in relation to susceptibility/resistance levels conferred by quantitative trait loci (QTL). We used a cut-petiole inoculation method coupled with both visual and PCR-based phenotyping at different time-points after inoculation, which revealed different kinetics of symptom development and pathogen growth among varieties. The results obtained with this method were partly consistent with field resistance phenotyping data, and allowed detection of the effect of at least two resistance QTL alleles introduced in near-isogenic lines. This method would be useful to compare a wider range of host varieties, to study the spectrum effect of resistance QTL or to decipher the mechanisms underlying this quantitative resistance.